Analysis of the Basic Principles of Ownership in Islam Perspective of Hadith Study - Fathoni, Khoirul (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Every economic system has characteristics, so a system deserves to be called an established economic system. No exception to the Islamic economic system. The property ownership model is among the unique features of the Islamic economic system. This study aims to determine the extent to which the principle of ownership in Islamic economics can be used as a basis from a hadith perspective. The method used in this research is a literature study using the Jamami'ul Kalim software to find the position and quality of hadith related to property ownership. In the search, it has been found several hadiths that do have the quality of sanad and Matan, which are classified as vital. However, some hadiths have dho'if qualities. The paper concludes that Islamic economics can be called an economic system that stands alone, which differs from capitalist and socialist systems based on the ownership model. Islamic economics offers 3 types of ownership: relative, individual, and general. Based on the hadith search, these 3 offers have their basis. According to the author's opinion, all three of them deserve to be used as the basis of ownership in Islam, even though there are weak hadiths in the general ownership section